Health education on disaster triage as an effort to change the attitudes of people living in tsunami-prone areas - Aesthetica Islamy; L. Lasman; Wiwid Yuliastuti; S. Suharyoto; Ria Anggraini; S. Suciati; N. Nurhidayati; Amita Audilla; Eny Masruroh (Journal of Community Service and Empowerment, 2023)
Indonesia as an archipelagic country located on the equator, between the continents of Asia and Australia and between the Pacific and Indian Oceans. Indonesia's geographical location lies on an unstable earth plate. Indonesia is also one of the disaster-prone areas, so that people in coastal areas must know what disaster management is most important to provide. This encourages community knowledge to provide first aid in a disaster situation using the principle of triage. The purpose of this activity is for the community to know about disaster management, especially the triage system in disaster-prone areas. The target of this activity is the community in Kalibatur Village, RT 05 RW 02, Kalidawir District, Tulungagung Regency. The implementation of this activity was carried out by pre-test and post-test. Data analysis was performed using the Wilcoxon Signed Range test analysis. Statistical test results obtained p value = 0.001 < α = 0.05. After the implementation of health education and counseling, the community has a positive attitude and a change in attitude regarding disaster triage as an effort to deal with and control victims of preventive natural disasters.